IDENTIFIKASI BAKTERI MRSA DAN KLEBSIELLA PNEUMONIA (ESBL) PADA ALAT VENTILATOR DI RUANG ICU RSUD X BATU - Retnani, Dyah Dwi; Dewi, Yulia Ratna (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Nosocomial infections in the ICU, especially those associated with the use of ventilators, most commonly occur as nosocomial pneumonia, or Hospital Acquired Pneumonia (HAP). Bacteria responsible for these infections include Methicillin-Resistant Staphylococcus aureus (MRSA) and Klebsiella pneumoniae producing Extended-Spectrum Beta-Lactamase (ESBL), which are of major concern due to their resistance to various antibiotics. This research is a descriptive quantitative study using a cross-sectional approach. The study was conducted in August 2024 in the Intensive Care Unit (ICU) of X Batu Hospital. The subjects of this study are ventilators used in the ICU of X Batu Hospital. The data collection process began by taking samples using a swab method on various surfaces of the ventilators in the ICU. The swabs were then immediately planted on culture media. The culture media were incubated under specific conditions to allow bacterial growth. Once bacterial colonies grew on the culture media, gram staining was performed. The next step involved bacterial identification using the BD phoenix™ 100, which automatically identifies bacterial species. The data were analyzed descriptively by frequency to determine the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) and Klebsiella pneumoniae (ESBL) bacteria growth. The study results showed no growth of MRSA and Klebsiella pneumoniae (ESBL) bacteria on ventilators before they were used by patients. However, Klebsiella pneumoniae (ESBL) growth was observed in 11.1% of ventilators used by patients in the ICU for more than 3 x 24 hours, excluding all other possible sources of infection prior to the patient's admission to the ICU.